Legality Of The Practice Of Wiretapping Methods Against Perpetrators Of Criminal Acts Of Corruption In The Provisions Of The Law On Criminal Acts Of Corruption - Dalimunthe, Aidil Putra (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2024)
Corruption cases in Indonesia continue to be a primary concern, especially since the perpetrators are often high-ranking government officials. Legally, corruption is governed by Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption Crimes, which defines this crime as unlawful acts that harm the national economy and contradict societal justice values. This study aims to explore the challenges faced in combating corruption and analyze its impact on public trust in the government. The research will employ a descriptive analysis method, focusing on literature studies from various sources related to the topic of this article. The findings indicate that, despite the government's various efforts, such as regulatory updates and the establishment of special agencies, public dissatisfaction regarding the effectiveness of anti-corruption measures remains prominent. Consequently, the government has implemented policies involving the interception of corruption offenders, which strengthens the evidence obtained for anti-corruption actions. The conclusion of this study is that while the government has strived to create justice in corruption cases, various challenges still persist in practice. Therefore, this research will propose new steps to prevent corruption offenders from proliferating further.